2007
DOI: 10.1007/s00192-007-0447-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of smooth muscle in the pathogenesis of pelvic organ prolapse—an immunohistochemical and morphometric analysis of the cervical third of the uterosacral ligament

Abstract: The uterosacral ligament (USL) is part of the pelvic floor connecting the uterus to the dorsal body wall and stabilizing it. In samples obtained from hysterectomy patients, the smooth muscle component of the cervical third of the USL was studied by smooth muscle actin (SMA) immunohistochemistry as indicator for structural abnormalities and by morphometric determination of nuclear size as measure for the functional state. From a total of 40 patients, 18 were matched according to age, parity, and premenopausal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
22
0
2
Order By: Relevance
“…Most investigators studied only the connective tissue part 20 and the smooth muscle content 21,22 of the uterine ligaments. Some studies discovered the presence of nervous and vascular elements within the connective tissue of the uterosacral ligament 26,27 and cardinal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most investigators studied only the connective tissue part 20 and the smooth muscle content 21,22 of the uterine ligaments. Some studies discovered the presence of nervous and vascular elements within the connective tissue of the uterosacral ligament 26,27 and cardinal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 There are only two studies which investigated the muscular content of the uterosacral ligament in women with prolapse. 20,21 The authors observed no difference in the amount of smooth muscle in uterosacral ligament in women with or without pelvic organ prolapse. In the round ligament, a significantly decreased smooth muscle fraction was morphometrically measured in H&E and Masson's trichrome slides from women with uterine prolapse.…”
mentioning
confidence: 95%
“…Parity, aging, and a chronic increase in abdominal pressure have been proven to be predisposing factors in the development of pelvic floor disorders ). There has also been growing evidence to support the role of genetics and disturbances in the extracellular matrix in the development of POP and UI Kerkhof et al, 2009;Reisenauer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have revealed a marked decrease and fragmentation of elastin fibers in patients with POP (Kerkhof et al, 2009;Reisenauer et al, 2008). Abnormal elastin homeostasis was also noted in women with stress UI (Soderberg et al, 2009;Goepel and Thomssen, 2006;Wen et al, 2007;Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The uterosacral ligament fixation is quite frequently used for vaginal vault suspension in uterine and vaginal vault prolapse [2][3][4][5]. Until now, most investigators studied only the ligamentous part [6,7] and the smooth muscle content [8] of the uterosacral ligament. However, pelvic autonomous nerves responsible for the viscerosensory innervation of the uterus, cervix, vagina, urethra, bladder, and rectum are known to course within the uterosacral "ligament" [9,10].…”
Section: Introductionmentioning
confidence: 99%